2017
DOI: 10.1038/nature20780
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory water effects link yearly global land CO2 sink changes to temperature

Abstract: Large interannual variations in the measured growth rate of atmospheric carbon dioxide (CO 2 ) originate primarily from fluctuations in carbon uptake by land ecosystems 1-3 . It remains uncertain, however, to what extent temperature and water availability control the carbon balance of land ecosystems across spatial and temporal scales 3-14 . Here we use empirical models based on eddy covariance data 15 and process-based models 16,17 to investigate the effect of changes in temperature and water availability on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
568
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 586 publications
(602 citation statements)
references
References 46 publications
33
568
0
1
Order By: Relevance
“…The need thus remains to reconcile the findings of temperature dominance on a large spatial scale and precipitation/moisture dominance on a fine scale. Recently, Jung et al (2017) suggested that the dominant role of soil moisture over land carbon-flux anomalies shifts to temperature when the scale of spatial aggregation increases, due to the compensatory water effects in the process of spatial upscaling. We also find that for all seasons except Q3, inversion-based land carbon-uptake anomalies in the tropics and southern extratropics are positively correlated with soil water content (data not shown), with 2015 having an extremely low soil water content anomaly in Q4, echoing the extreme high-temperature anomaly shown in Fig.…”
Section: Seasonal Land Carbon-uptake Transitions In the Tropics And Imentioning
confidence: 99%
“…The need thus remains to reconcile the findings of temperature dominance on a large spatial scale and precipitation/moisture dominance on a fine scale. Recently, Jung et al (2017) suggested that the dominant role of soil moisture over land carbon-flux anomalies shifts to temperature when the scale of spatial aggregation increases, due to the compensatory water effects in the process of spatial upscaling. We also find that for all seasons except Q3, inversion-based land carbon-uptake anomalies in the tropics and southern extratropics are positively correlated with soil water content (data not shown), with 2015 having an extremely low soil water content anomaly in Q4, echoing the extreme high-temperature anomaly shown in Fig.…”
Section: Seasonal Land Carbon-uptake Transitions In the Tropics And Imentioning
confidence: 99%
“…Thus, we assessed the spatial coherence of simulated patterns of SWE and W by calculating the proportion of total positive and total negative covariances among grid cells (Eqs. 4 and 5 in Jung et al, 2017). If the sum of positive covariances outweighs the sum of negative covariances, it implies some degree of spatial coherence of the anomalies.…”
Section: Analysis Of Tws Variations and Compositionmentioning
confidence: 99%
“…soil moisture anomalies, have much larger spatial variability than others. Due to this high smallscale heterogeneity, the effect on larger regional scale might be smaller than expected, as different local scale heterogeneities compensate for each other when the regional averages are calculated (Jung et al, 2017). Thus, we assessed the spatial coherence of simulated patterns of SWE and W by calculating the proportion of total positive and total negative covariances among grid cells (Eqs.…”
Section: Analysis Of Tws Variations and Compositionmentioning
confidence: 99%
“…We perform the REA procedure three times using different observationally constrained estimates of current NPP: retrievals of the terrestrial carbon cycle with the CARbon DAta Model fraMework (CARDAMOM; model-data fusion approach (Bloom and Williams, 2015a;, an approximation of NPP based on the up-scaled FLUXCOM gross primary productivity (GPP) datasets Jung et al, 2009Jung et al, , 2011Jung et al, , 2017Tramontana et al, 2016) and the MOD17A3 MODIS NPP product (Running et al, 2004;Zhao et al, 2005;Zhao and Running, 2010). Based on optimally weighted model averages, we evaluate the impact of the REA method on 21st century projections of NPP but also on the uncertainty in the future resilience of the CO 2 fertilization that exists among the models.…”
mentioning
confidence: 99%